Perancangan Enterprise Architecture Pada SMKN1 di Pulau Bangka Menggunakan Metode Zachman Framework - Francka Sakti Lee; Steven Steven (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
SMKN1 on the island of Bangka is a school located in the Bangka area. Currently, SMKN1 already uses and implements IS/IT to carry out its business processes. There are several problems in schools such as a website system that cannot be accessed, student attendance records are done manually so that recording errors often occur, and errors in recording the names of students who have attended extracurricular due to the large number of students. Therefore, we need an IS/IT design that can support the company's ongoing business processes. In this study, research and design were carried out with the application of enterprise architecture. The framework used in this article is the Zachman framework. In this paper, a complete perspective is not used, only using a 4x5 perspective because the process is not carried out until the implementation, the process is carried out only until the design. The result of the design is in the form of an IS/IT system blueprint. Suggested applications are school websites, e-library websites, attendance websites, procurement systems, and extracurricular websites.